Eating disorders in midlife women: A perimenopausal eating disorder?. (March 2016) - Baker, Jessica H.; Runfola, Cristin D.
Highlights: Eating disorders are erroneously stereotyped as a disease of adolescence and young adulthood. Midlife eating disorders may be detrimental due to the body's lessened ability to fight disease and physical insult. Perimenopause, or the menopause transition, may be a significant period of vulnerability for the development, exacerbation, or relapse of eating disorder symptoms. Risk for eating disorder symptoms at perimenopause may, in part, be due to the changes in estrogen that occur at time. Women with an eating disorder at perimenopause may represent a hormone-sensitive eating disorder phenotype. Abstract: Eating disorders afflict women across the lifespan with peak onset during critical or sensitive developmental periods of reproductive hormone change, such as puberty. A growing body of research supports the role of reproductive hormones, specifically estrogen, in the risk for eating disorders and related symptomatology in adolescence and young adulthood. Like puberty, perimenopause is characterized by estrogen change and may also present a window of vulnerability to eating disorder development. Here, we discuss the evidence that suggests perimenopause indeed may be a vulnerable period for the development or redevelopment of an eating disorder for midlife women. Drawing from what is known about the influence of estrogen on eating disorders at younger ages and from other psychiatric disorders with similar risk trajectories (i.e., perimenopausal depression), we describe a potential mechanism of risk for a perimenopausal eating disorder and how this can be explored in future research. Investigating vulnerability to perimenopausal eating disorders will clarify eating disorder etiology, identify reproductive stage-specific risk profiles, and guide future treatment directions.